EVALUASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Anggraeni, Rani; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the tax administration system that includes organizational structure, organizational strategy, organizational procedures, and organizational culture to the tax compliance at KPP Pratama Surabaya Wonocolo. This research is quantitative. The population is all taxpayers both individual and corporate who are registered KPP Pratama Surabaya Wonocolo. The sample has been done by employing accidental sampling technique and 65 taxpayers who are registered at KPP Pratama Surabaya Wonocolo have been selected as respondents. The data which has been uses in this research are the primary data which has ben obtained by issuing questionnaires and the secondary data has been obtained through library research. This research has been done by using multiple linear regression analysis. The result of the research indicates that partially the organizational structure, organizational strategy, organizational procedures, and organizational culture have positive influence to the tax compliance. Meanwhile, simultaneously the tax administration systems (i.e.: organizational structure, organizational strategy, organizational procedures, and organizational culture) have an influence on the taxpayer compliance. It means that the presence of tax administration systems can improve taxpayer compliance, particularly at KPP Pratama Surabaya Wonocolo.Keywords: Tax Administration System, Organizational Structure, Taxpayer Compliance.